From Plate To Patient: Engineering A Circular Economy Model For Hospital Food Waste And Green Initiatives (International Journal of Environmental Sciences, 2025)
Hospitals generate significant volumes of food waste daily, creating both operational challenges and opportunities for sustainable resource management. Facility management units often lead green initiatives such as composting, where food waste is converted into organic fertilizer and distributed to external farmers. While this practice reduces landfill burden, it typically remains a linear process with limited benefits to the hospital itself. This study develops a circular economy model for hospital food waste, emphasizing quantitative measurement of waste generation, composting capacity, and compost yield. Food waste streams from inpatient kitchens and cafeterias were tracked to determine daily and monthly volumes, while composting outputs were analyzed in terms of nutrient-rich end products. The research focuses on the composting process through aerobic decomposition using a mechanical composter to assess its suitability for hospital food waste management. The proposed model closes the gap between waste disposal and hospital benefit: compost generated on-site is supplied to local farmers, who in turn return fresh produce that can be reintegrated into hospital kitchens and patient meals. This cycle from plate to patient not only reduces disposal costs but also strengthens hospital food supply resilience, promotes local farming, and aligns with national green policies of the Ministry of Health Malaysia (MOH). By positioning facility management as a driver of circular resource systems under the Sustainability Program, this research demonstrates how hospitals can transform food waste from a disposal problem into a strategic resource for patient care and sustainable healthcare delivery. By seeing the advantages, such as nutrient recovery, cost efficiency, and scalability, with the potential drawbacks, including operational complexity, cultural acceptance, and regulatory challenges, this research highlights the trade-offs that influence practical adoption. Ultimately, the findings aim to provide a decision-making framework for healthcare facilities to integrate food waste valorization into broader sustainability agendas, thereby advancing hospitals not only as centers of treatment but also as active contributors to environmental stewardship and resource innovation.